Comportamento mecânico de poli(éter-éter-cetona) revestida com hidroxiapatita por aspersão plasma para uso em implantes cirúrgicos - Oliveira, Thiago Patrício de (2015)
The remarkable advances in scientific research of materials for ever demanding service requirements has led to novel developments of biomaterials, especially in the field of surgical implants. In this field, the semi-crystalline thermoplastic PEEK (poly-ether-ether-ketone) has been selected as one of the most suitable for orthopaedic applications. Due to its excellent short and long term mechanical properties and also associated to its elastic modulus compatibility with that of the human bone, the polymer safely fulfills the mechanical and biological requirements for injection moulded implants with complex design. However, as also verified with metallic implants, the PEEK osteointegration is slow and, therefore, can be enhanced with bioactive ceramics coatings of hydroxyapatite (HA), obtained mostly using plasma spray technique. However, as the high temperatures related to the plasma process can impair significantly its mechanical performance, this study aims to investigate the influence of the plasma spray process on the mechanical fatigue behaviour of injection moulded PEEK coated with HA. Using mechanical test specimens with three distinct treatments: (i) PEEK as molded, (ii) PEEK with thermal plasma shock and (iii) HA plasma coated PEEK, several characterization techniques, which include X-ray diffraction, differential scanning calorimetry (DSC), short-term tensile and flexural tests, dynamic-mechanical thermal analysis (DMTA) and deformation-controlled flexural fatigue tests were performed. The quality of HA coating was considered adequate, as identified by X-ray and SEM analysis. The experimental data on the main mechanical characterization of HA coated PEEK, demonstrated that the plasma treatment contributes to a significant increase in the short-term flexural elastic modulus and strength properties and also reduces the stress relaxation rate (residual stress) during the fatigue cycling up to one million cycles. These increases in the flexural stiffness and residual fatigue stress of PEEK are induced by a increase in the polymer crystallinity content and the presence of additional thermal residual surface stresses on the PEEK surface exposed to the plasma thermal shock, as identified by DSC and DMTA analysis.